Experimental Investigation on Self-Compacting Concrete with Waste Carbon Black - Shober Saheb Alyhya, Wajde; Alaa Abed Alameer, Shober Saheb Alyhya; Mohammed Ridha Mahmmod, Laith; ., . (International Journal of Engineering and Technology, 2018)
One of the vital aspects in designing self-compacting concrete (SCC) is the amount and type of filler with respect to cement and water. These have a great impact not only on fresh SCC properties (segregation, filling, fluidity, etc.) but also on its hardened properties. In this experimental study, an attempt was conducted to diminish the pores occurrence in SCC by using carbon black as a filler, which is a waste from the rubber industry. The experimental work investigates the SCC properties when crusher dust filler from the aggregate plant was partially replaced by waste carbon black. SCC mixes of two carbon black replacement ratios (2.5% and 5%) were studied to reveal its effect on the fresh and hardened properties, through various tests. The fresh properties were investigated by means of slump flow (t500), J-ring and L-box. The compressive and splitting tensile strengths tests were implemented along with the mix density evaluation to characterize the hardened properties of SCC with black carbon. It has been found that the carbon black has a useful role for the fresh properties of SCC. Indeed, the carbon black provides superior performance for the compressive strength development than crusher dust. In contrast, it slightly worsened SCC splitting tensile strength.Â Â